Atmospheric deposition as a source of carbon and nutrients to an alpine catchment of the Colorado Rocky Mountains - Mladenov, Natalie; Williams, M. W.; Schmidt, S. K.; Cawley, K. (My University, 2012)
Many alpine areas are experiencing deglaciation, biogeochemical changes driven by temperature rise, and changes in atmospheric deposition. There is mounting evidence that the water quality of alpine streams may be related to these changes, including rising atmospheric deposition of carbon (C) and nutrients. Given that barren alpine soils can be severely C limited, atmospheric deposition sources may be an important source of C and nutrients for these environments. We evaluated the magnitude of atmospheric deposition of C and nutrients to an alpine site, the Green Lake 4 catchment in the Colorado Rocky Mountains. Using a long-term dataset (2002–2010) of weekly atmospheric wet deposition and snowpack chemistry, we found that volume weighted mean dissolved organic carbon (DOC) concentrations were 1.12±0.19 mg 1ˉ¹, and weekly concentrations reached peaks as high at 6–10 mg 1ˉ¹ every summer. Total dissolved nitrogen concentration also peaked in the summer, whereas total dissolved phosphorus and calcium concentrations were highest in the spring. To investigate potential sources of C in atmospheric deposition, we evaluated the chemical quality of dissolved organic matter (DOM) and relationships between DOM and other solutes in wet deposition. Relationships between DOC concentration, fluorescence, and nitrate and sulfate concentrations suggest that pollutants from nearby urban and agricultural sources and organic aerosols derived from sub-alpine vegetation may influence high summer DOC wet deposition concentrations. Interestingly, high DOC concentrations were also recorded during “dust-in-snow” events in the spring, which may reflect an association of DOM with dust. Detailed chemical and spectroscopic analyses conducted for samples collected in 2010 revealed that the DOM in many late spring and summer samples was less aromatic and polydisperse and of lower molecular weight than that of winter and fall samples. Our C budget estimates for the Green Lake 4 catchment illustrated that wet deposition (9.9 kg C haˉ¹ yrˉ¹) and dry deposition (6.9 kg C ha ˉ¹ yr ˉ¹) were a combined input of approximately 17 kg C ha ˉ¹ yr ˉ¹, which could be as high as 24 kg C ha ˉ¹ yr ˉ¹ in high dust years. This atmospheric C input approached the C input from microbial autotrophic production in barren soils. Atmospheric wet and dry deposition also contributed 4.3 kg Nha ˉ¹ yr ˉ¹, 0.15 kg P ha ˉ¹ yr ˉ¹, and 2.7 kg Ca2+ ha ˉ¹ yr ˉ¹ to this alpine catchment.
Keywords: Atmospheric deposition; Rocky Mountains; Colorado